PENERAPAN METODE QIRA’AH DALAM PEMBELAJARAN BAHASA ARAB DI MTSS IBADURRAHMAN STABAT TAHUN AJARAN 2024/2025 - Mardhiyah, Rodhiatan; Budi Harjo (Universitas Negeri Semarang, 2025)
Arabic holds a unique position for Muslims and for anyone who studies it. The language feels familiar due to its frequent use in religious practices such as prayer and supplication, yet it is also perceived as difficult due to its complexity in learning. Nevertheless, Arabic is the only language that paves the way to understanding the highest sources of Islamic knowledge—the Qur'an and Hadith. This study is motivated by the low motivation and poor learning outcomes of students in Arabic language instruction at MTsS Ibadurrahman Stabat. This condition is primarily caused by the lack of variation in teaching methods used by teachers, leading to student boredom and low classroom engagement. The purpose of this study is to examine the implementation of the Qirā’ah method in enhancing Arabic learning, identify the challenges faced during its application, and explore the efforts made to overcome these obstacles. The research employs a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The findings reveal that the application of the Qirā’ah method improves students' vocabulary comprehension and reading skills in Arabic. However, its implementation also faces several challenges, such as students' low interest, time constraints, and limited learning media. Efforts to address these issues include providing motivation, utilizing engaging teaching aids, and assigning varied tasks. In conclusion, the Qirā’ah method can serve as an effective alternative for improving the quality of Arabic language instruction in schools.